Effect of 8% Purple Sweet Potato Extract Cream on Wrinkle Reduction, Skin Moisture, and Elasticity - Laksmi, I Gusti Ayu Agung Mini; Praharsini, I Gusti Ayu Agung; Rusyati, Luh Made Mas; Suryawati, Nyoman; Winaya, Ketut Kwartantaya; Karmila, I Gusti Ayu Agung Dwi (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Purple sweet potato has been shown to contain anthocyanins, polyphenols, flavonoids, and tannins that act as antioxidants and have the potential to correct signs of aging in the skin, such as wrinkles, lack of hydration, and pigmentation. Purpose: to known the potential of 8% purple sweet potato extract for wrinkles, moisture, and elasticity. Methods: A one-group experimental study with pre and post-test assessment. The subject is women with photoaging aged 30-45 years. A pre-test was conducted by examining wrinkles using the Glogau scale and a simple A-one scanner, treatment with 8% purple sweet potato extract cream for 6 weeks, and then a post-test at the end of the 6th week to check wrinkles, moisture, and elasticity using a simple A-one scan. Statistical tests using the SPSS program, version 25.0. The analysis performed was descriptive statistical and comparative analysis using a paired T test. Result: A total of 25 respondents with a mean age ± SD of 38.22 ± 4.23 years, the most Glogau scale in type 2 is 22 respondents (88%), the most sun exposure for 30 minutes per day is 14 respondents (56%). The degree of wrinkles decreased after treatment -4.960±1.353 [95% CI -7.681-(-2.239); P=0.001]. The degree of moisture increased after treatment 8.840±2.990% (95% CI 2.829-14.851; P=0.005. The degree of elasticity increased after treatment 14.840±4.623 (95% CI 5.544-24.136; P=0.002). Conclusion: 8% purple sweet potato extract can reduce the degree of wrinkles, improve the degree of skin moisture, and improve the degree of skin elasticity.